Effect of seaweed canopy disturbance on understory microbial communities on rocky shores - Gonzalez, Sebastian Vadillo (2024)
Introduction: The collapse of macroalgal habitats is altering the structure of benthic communities on rocky shores globally. Nonetheless, how the loss of canopy-forming macroalgae influences the structure of epilithic microbial communities is yet to be explored. Methods: Here, we used experimental field manipulations and 16S-rRNA-gene amplicon sequencing to determine the effects of macroalgal loss on the understory bacterial communities and their relationship with epiphytic bacteria on macroalgae. Beds of the fucoid Hormosira banksii were exposed to different levels of disturbance resulting in five treatments: (i) 100% removal of Hormosira individuals, (ii) 50% removal, (iii) no removal, (iv) a procedural control that mimicked the removal process, but no Hormosira was removed and (v) adjacent bare rock. Canopy cover, bacterial communities (epilithic and epiphytic) and benthic macroorganisms were monitored for 16 months. Results: Results showed that reductions in canopy cover rapidly altered understory bacterial diversity and composition. Hormosira canopies in 50% and 100% removal plots showed signs of recovery over time, but understory epilithic bacterial communities remained distinct throughout the experiment in plots that experienced full Hormosira removal. Changes in bacterial communities were not related to changes in other benthic macroorganisms. Discussion: These results demonstrate that understory epilithic bacterial communities respond rapidly to environmental disturbances at small scales and these changes can be long-lasting. A deeper knowledge of the ecological role of understory epilithic microbial communities is needed to better understand potential cascading effects of disturbances on the functioning of macroalgal-dominated systems.